Implementation of Islamic Values in Muslim Women Entrepreneurship: A Qualitative Approach to Case Study at Bakso Lava Ummu Akbar - Dina Marni; Dwi Meutia Hasni (Sean Institute, 2026)
The involvement of Muslim women in the Indonesian business world is growing rapidly, but in-depth studies on the internalization of sharia values ​​​​in everyday business practices are still very limited. This study aims to explore how a Muslim entrepreneur integrates Islamic principles into all aspects of her business management. The approach used is a qualitative single instrumental case study with data collection techniques in the form of in-depth semi-structured interviews, field observations, and documentation studies of the Bakso Lava Ummu Akbar business in the Deli Serdang and Medan areas. The results show that the entrepreneurial motivation of business owners stems from the drive for financial independence of Muslim women and the need to maintain sharia identity in a professional environment. The implementation of Islamic values ​​​​is realized through the guarantee of halal thayyiban products, a taqwa-based employment system, usury-free financial management, and da'wah programs such as murottal readings and the establishment of free Qur'an Houses. The resulting impact is multidimensional, including the creation of more than one hundred jobs, strengthening the local economic ecosystem, social empowerment, and increasing the spiritual awareness of the surrounding community. This study concludes that internalization of maqāṣid al-syarī'ah on a micro-business scale is not an obstacle, but rather the foundation of authentic and sustainable competitive advantage.